2011
DOI: 10.1111/j.1365-2753.2010.01629.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of hospital falls on long‐term care wards in Japan

Abstract: Many patients on long-term care wards in Japan were elderly and experienced falls during their hospital stay, with consequent injuries. Taking into account the risk factors identified, we need to devise effective strategies to prevent falls and related injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
2
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 21 publications
1
30
2
10
Order By: Relevance
“…Another risk factor that is approached in different ways includes assessing the mobility of patients that is described as changed, with loss of balance, difficulty in gait and sensory disabilities (16,38,66) .…”
Section: Discussionmentioning
confidence: 99%
“…Another risk factor that is approached in different ways includes assessing the mobility of patients that is described as changed, with loss of balance, difficulty in gait and sensory disabilities (16,38,66) .…”
Section: Discussionmentioning
confidence: 99%
“…Falls are one of the most frequently reported adverse events in hospitals 1,2 and occur in between 13-23% of patients. 3,4,5 Between 23-42% of falls in hospital are associated with physical injuries, 3,4,6,7 of which between 2-7% result in hip fractures. 8,9 Results from several meta-analyses have suggested that multifactorial falls prevention interventions 10,11,12 and nonpharmacological delirium interventions 13 can be effective in reducing the number of falls in hospitals, although one recent large-scale multifactorial intervention study conducted in acute wards 14 showed no difference in falls or fall injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Each year, approximately 30.0% to 50.0% of persons living in institutions suffer falls and about 40.0% of them experience recurrent falls. 12 , 21 In hospitals, the incidence of falls for persons aged 60 or over ranges between three and seven falls per 1,000 patients/day 6 , 7 , 22 and is related to factors intrinsic to the patient, such as age, balance and gait deficit, urinary incontinence, compromised cognitive status, and others. 5 , 7 , 22 Extrinsic factors are represented by some conditions of the hospital environment and situations related to healthcare by the hospital medical staff, such as use of hypnotic drugs, anxiolytics, and antiparkinsonism medicines, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Falls can cause fractures, soft tissue injuries, bruises, lacerations and death. 6 , 22 In addition to the physical damage, caregivers and family near these seniors have higher prevalence of psychoemotional disorders. 14 , 19 Accidents by falls in hospitals also cause damage to the institutions, since they are associated with increased hospital stay and increased use of health resources.…”
Section: Introductionmentioning
confidence: 99%